Draft Annual Plan Rajasthan 1979-80 - Planning Commission (Planning Commission, 1979)
Consistent fifth the objectives and strategy indicated in the Government of India's Draft Five Year Plan(1978-83) document, and as enunciated in Rajasthan's Draft Five Year Plan 1978- 83, while formulating the State's proposals for Annual Plan 1979- 80 tie basic objectives kept in view are substantial reduction in the unemployment/under employment and poverty provision of minimum needs for poor, reduction in inequalities, along with a higher rate of growth and a rural bias. Followed for determining the sectoral allocations are as indicated below.
Planning Department, Government of Rajasthan